Performance Analysis of Pulse Shaping Filters for GFDM Systems - Kalsotra, Surbhi (TIET, 2018)
During the previous years, the evolution of mobile communication networks has been done in terms of number of users and throughput. But higher throughput will not be enough to address the fifth generation of cellular networks. Cellular systems of the fourth generation (4G) have been optimized to provide high data rates and reliable coverage to mobile users. Cellular systems of the next generation will face more diverse application requirements like the demand for higher data rates exceeding 4G capabilities, battery-driven communication sensors need ultra-low power consumption; and control applications require very short response times. We use a waveform technique called as Generalized Frequency division Multiplexing (GFDM) to achieve these requirements. Various generations of mobile networks, 5G waveform techniques, standard projects under 5G are discussed. Literature survey has been done by considering papers related with the GFDM technique. From these papers, observations have been drawn and which is used to formulate the problem. Finally the objectives have been drawn in which different pulse shaping filters are used in GFDM technique. Finally, simulation results are computed by using MATLAB R2017a in which symbol error rate performance and out of band emissions power performance have been improved. Finally, the conclusion and the future scope of the work has been discussed.
Master of Engineering- EC
Keywords: 5G; Filters; Pulse shaping; GFDM; SER; Pulse shaping filters